2019
DOI: 10.3390/ijms20102514
|View full text |Cite
|
Sign up to set email alerts
|

Positive Effects of Heme Oxygenase Upregulation on Adiposity and Vascular Dysfunction: Gene Targeting vs. Pharmacologic Therapy

Abstract: Objective: Heme oxygenase (HO-1) plays a critical role in adipogenesis and it is important to understand its function in obesity. Many studies have shown that upregulation of HO-1 can affect the biologic parameters in obesity-mediated diabetes, hypertension and vascular endothelial cell function. Thus, we aimed to explore the hypothesis that upregulation of HO-1, using a pharmacologic approach as well as gene targeting, would improve both adiposity and endothelial cell dysfunction by direct targeting of endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 48 publications
2
29
0
1
Order By: Relevance
“…In this study, we demonstrate that adipocyte-specific HO-1 expression improves adipocyte hypertrophy by decreasing cell size (Figure 1); the progression of obesity is tightly associated with increased adipocyte hypertrophy [24,25,40]. An increase in adipocyte cell size is negatively correlated with adiponectin levels [22].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In this study, we demonstrate that adipocyte-specific HO-1 expression improves adipocyte hypertrophy by decreasing cell size (Figure 1); the progression of obesity is tightly associated with increased adipocyte hypertrophy [24,25,40]. An increase in adipocyte cell size is negatively correlated with adiponectin levels [22].…”
Section: Discussionmentioning
confidence: 63%
“…ROS plays a major role in reprogramming a normal adipocyte phenotype to inflamed adipocytes, resulting in adiposopathy [22][23][24]. Affected adipocytes proceed to terminal differentiation and inflammation, resulting in adipocyte dysfunction [23,25]. Obese animal models have low levels of HO-1 and are therefore more susceptible to oxidative stress and cytotoxicity caused by a build-up of heme, a pro-oxidant, and ROS [1,24,26].…”
Section: Introductionmentioning
confidence: 99%
“…The same group, more recently focused on long-term endothelial HMOX1 activation in mice fed a HFD demonstrating the gene therapy to increase expression of HMOX1, reduced ICAM and VCAM expression, decreased serum markers of inflammation, such as IL-1 and TNFα, reduced the size of adipocytes and down-regulated PPARγ. Furthermore, these effects were prevented by using a specific inhibitor of HMOX1 activity, indirectly suggesting that the ability to restore a proper crosstalk between the vasculature and adipocytes depends on the metabolic products of endothelial HMOX1 activity (Peterson et al, 2019). Together these findings demonstrate that endothelial activation of HMOX1 could play an important role in the treatment/prevention of obesity, and further highlight the importance of AMPK-dependent signaling in mediating the anti-obesogenic effects of bilirubin.…”
Section: Bilirubin and Obesitymentioning
confidence: 80%
“…AngII, angiotensin II; BRT, bilirubin ditaurate; BLVRA, biliverdin reductase; CAD, coronary artery disease; CO, carbon monoxide; CoPPIX, cobalt protoporphyrin IX; CRC, colorectal cancer patients; db/db, diabetic mice; DIO, diet-induced obese; DM, diabetes mellitus; DSS, dextran sodium sulfate; EAE, experimental autoimmune encephalomyelitis; FMD, fasting-mimicking diet; FVB, friend leukemia virus B; GI, gastro-intestinal; GS, Gilbert Syndrome; HFD, high fat diet; IRI, ischemia/reperfusion injury; Ldlr −/− , low-density lipoprotein receptor-deficient mice; MCAO, middle cerebral artery occlusion; MS, multiple sclerosis; OVA, ovalbumin; PMBCs, peripheral blood mononuclear cells; RA, rheumatoid arthritis; SHR, spontaneously hypertensive rat; SJL, Swiss Jim Lambert mice; SLE, systemic lupus erythematosus; SnPP, tin protoporphyrin IX; STS, short-term starvation; STZ, streptozocin; UCB, unconjugated bilirubin; UTG1A1, uridine diphpspho-glucuronosyl transferase 1A1; ZnPP, zinc protoporphyrin IX; WKI, Wistar Kyoto rat. cEPCs 10-20 mg/dl Progenitor endothelial cells induced to proliferate when exposed to 5 mg/dl bilirubin; higher concentrations (up to 20 mg/dl) induce cell death Jabarpour et al, 2018 EA.hy926 0.5-100 µM Exogenous bilirubin increases endothelial antioxidant activity as well as HMOX1-dependent bilirubin generation Ziberna et al, 2016 Commercially EC Not evaluated EC-transfected with HMOX1 release substances that increase healthy adipocytes Peterson et al, 2019 Human and non-human EC HUVECs and H5V cells 0.015 µM < Bf < 0.030 µM UCB, at clinically relevant concentrations, limits over-expression of adhesion molecules and inhibits PMN-endothelial adhesion induced by pro-inflammatory cytokine TNFα, even though UCB itself does not alter expression of these adhesion molecules. Inhibition NF-kappaB transduction pathway Mazzone et al, 2009a,b HAECs and mAECs Not evaluated In HAECs and in primary mAECs from HMOX1 +/+ and HMOX1 −/− , SDF-1 (100-200 ng/ml) favors angiogenesis through the induction of HMOX1 Deshane et al, 2007 (Continued) ( Deshane et al, 2007).…”
Section: Bilirubin and Wound Healingmentioning
confidence: 99%
“…We showed that MG administration increased the expression of HO-1 and SOD2 by promoting the translocation of Nrf2 into the nucleus. The induction of HO-1 and SOD2 led to the alleviation of oxidative stress and conferred resistance to inflammatory insults [ 6 , 43 ]. HO-1 is the rate-limiting enzyme of heme catabolism, which catalyzes the cellular heme to carbon monoxide (CO), biliverdin, and free iron and exerts significant anti-inflammatory effects [ 44 ].…”
Section: Discussionmentioning
confidence: 99%